Proposed new interior design scheme of UiTM Art Gallery for I&P Group Sdn. Bhd. at Alam Impian Sales Gallery at No 1, Jalan Panglima Hitam 35/26 Seksyen 35,40470 Shah Alam, Selangor Darul Ehsan / Wan Nuranis Sorfina Wan Mohd Rozi - Wan Mohd Rozi, Wan Nuranis Sorfina (Faculty of Architecture, Planning and Surveying, 2011)
The project that had been chosen for the final project is to Proposed New Interior Design Scheme for UiTM Art Gallery for l&P Group Sdn. Bhd. at Alam Impian Sales Gallery at no 1,Jalan Panglima Hitam 35/26 Seksyen 35, 40470 Shah Alam, Selangor Darul Ehsan. The idea of this new UiTM Art Gallery to be designed in such a way that will benefits and increase the properties value of Alam Impian Township. Moreover, the purpose of this proposed art gallery is to atrract the residentials and public to go to the gallery for arts educations which there will be an art event and any other speacial events such as Gallery Talks & Tours. An Art Gallery would help others to appreciate the creative and innovative works of artists that incautiously affecting the circle of life. The building for this project is a single standing building that function as a Sales Gallery for the township of Alam Impian but also well-designed a specific space for an art gallery. Because of the collabration of l&P Group and Universiti Teknologi Mara's aspiration of bringing arts out beyond lecture theatres and into practice in the industry, the art gallery is then reserved for UiTM to present and promote the artworks of both established and emerging artists from the students of UitM itself. This proposed new UiTM Art Gallery is situated at the top of the hill of Alam Impian’s lake park that exhibit art in every possible manner where people are enjoying the calm environtment thus inspired to enjoy healthy and creative activities.